2021
DOI: 10.3390/antiox10081222
|View full text |Cite
|
Sign up to set email alerts
|

Lupinus angustifolius Protein Hydrolysates Reduce Abdominal Adiposity and Ameliorate Metabolic Associated Fatty Liver Disease (MAFLD) in Western Diet Fed-ApoE−/− Mice

Abstract: Metabolic-associated fatty liver disease (MAFLD) is the most important cause of liver disease worldwide. It is characterized by the accumulation of fat in the liver and is closely associated with abdominal obesity. In addition, oxidative stress and inflammation are significant features involved in MAFLD. Recently, our group demonstrated that lupin protein hydrolysates (LPHs) had lipid lowering, antioxidant, and anti-inflammatory effects. Sixty male mice fed with a Western diet were intragastrically treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…Moreover, liver CHOL, NEFA, and TG levels were significantly elevated by fasting in G23Rik -/mouse livers when compared to fasted wildtype animals. Expression of Cd36, a PPARA-regulated long chain fatty acid transporter and an important marker for metabolic-associated fatty liver disease 29,30 , was significantly elevated in livers of fasting G23Rik -/mice compared to G23Rik +/+ mice, which may contribute to the observed hepatosteatosis in G23Rik -/livers. Thus, G23Rik has a negative regulatory effect on Cd36 expression under fasting conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, liver CHOL, NEFA, and TG levels were significantly elevated by fasting in G23Rik -/mouse livers when compared to fasted wildtype animals. Expression of Cd36, a PPARA-regulated long chain fatty acid transporter and an important marker for metabolic-associated fatty liver disease 29,30 , was significantly elevated in livers of fasting G23Rik -/mice compared to G23Rik +/+ mice, which may contribute to the observed hepatosteatosis in G23Rik -/livers. Thus, G23Rik has a negative regulatory effect on Cd36 expression under fasting conditions.…”
Section: Discussionmentioning
confidence: 97%
“…S3, Table S3). Furthermore, hepatic expression of Cd36, a long chain fatty acid transporter and PPARA target gene 29,30 , was significantly elevated in fasting G23Rik -/mice compared to fasting G23Rik +/+ mice (Fig. 5E).…”
Section: Loss Of G23rik Potentiates Lipid Accumulation During Physiol...mentioning
confidence: 96%
“…The activity of these enzymes was elevated with MLPH treatment in a dose-dependent manner. Santos-Sanchez et al [ 57 ] also reported that treatment with Lupinus angustifolius protein hydrolysates boosted hepatic total antioxidant capacity, and then decreased hepatic inflammation and abdominal obesity in western diet-fed-apoE-/- mice. In the present study, the degradation of hepatic antioxidant enzyme activity in the CON group was effectively inhibited by MLPH treatment, suggesting that MLPH treatment is favorable to increase antioxidant effects in ob / ob mice.…”
Section: Discussionmentioning
confidence: 99%
“…LDPs are also able to suppress lipid synthesis and accumulation and improve antioxidant and anti-inflammatory status after oral ingestion of LPHs by animal model of obesity [ 127 ]. Another useful observation has been provided by a recent clinical study that has shown that the consumption of 30 g/day lupin protein for three months reduced the plasma PCSK9 level by 12.7% [ 125 ].…”
Section: Biological Activities Of Ldpsmentioning
confidence: 99%